Impact of cover crops and rainfall distribution on Scaptocoris castanea (Hemiptera: Cydnidae) - José Ednilson Miranda; Alexandre Cunha de Barcellos Ferreira; Ana Luíza Dias Coelho Borin; João Luis da Silva Filho; Bruna Mendes Diniz Tripode; André Luís Barbieri; Oscar Gonçalves do Nascimento Neto (Pesquisa Agropecuária Brasileira, 2022)
Abstract The objective of this work was to evaluate the population dynamics of the burrower bug (Scaptocoris castanea) in an area with cotton (Gossypium hirsutum) cultivated after cover crops. The insects were counted in soil samples collected at 0-40 cm depth. Insect incidence was documented in 18 cover crops, alone or intercropped, in each plant stage. Rainfall distribution was compared with fluctuations in the burrower bug population. Crotalaria species have a suppressive effect on the insect population, whereas some grass species favor its increase. Rainfall distribution directly influences the insect population.